Structural model and features of the world-class Cuiabá orogenic gold deposit, Rio das Velhas greenstone belt, Quadrilátero Ferrífero region, Brazil - Fernandes, Raphael do Carmo; Roncato, Jorge; Sérgio de Paula, Rodrigo (Journal of South American earth sciences, 2023)
The structural architecture of an orogenic deposit is essential for its metallogenetic understanding, as both subjects are interconnected in this type of environment. Cuiabá gold deposit, located in Archean rocks from Rio das Velhas Greenstone Belt, is the subject of numerous studies focused mainly on metallogenetic issues. From the point of view of structural characterization, two divergent models have been studied: the sheath-fold model and the refolding model. Such hypothesis is different in terms of defining an exploratory research plan and, therefore, the detailed structural characterization is still not well understood. As a way of filling this gap, the main objective of this work is to propose a structural characterization of the entire deposit in order to demonstrate evidence for a new model of tectonic evolution. For this, the methodologies applied for this work were: underground geological mapping in all available ore galleries and definition of geological-structural domains whose main criteria are related to down-plunge view of fold asymmetry and stratigraphic indicators. Structural geology is characterized by 3 deformation phases related to 2 tectonic events. The first event has two ductile-progressive deformation phases (D1 and D2), with NE-SW strike-slip direction of transport associated coaxial fold interference patterns with cylindrical geometry plunging to ESE, which represents the main structure at the mine. The second event is a brittle-ductile deformational phase (D3) with W-verging reverse fault systems, probably associated to Brasiliano Pan-African Orogeny. Gold mineralization is associated with silica and sulfide-rich hydrothermal fluid introduction through D1 and D2 axial-plane foliation. Phase D1 is pyrrhotite-associated mineralization, with coarse gold presence. D2 phase has pyrite-associated mineralization with fine gold. There is no gold in phase D3, although it has late-tectonic sulphides formation. Therefore, there is no field evidence that corroborate the existence of sheath folds for the deposit. Fold interference patterns associated to deposit morphology suggests SW and N prospective targets, with strong possibility of structural connection between other gold deposits, such as Lamego and Descoberto targets. •Geological mapping reveals a pre-Cambrian fold interference pattern with no field evidence for sheath folds.•Gold inside BIF is related to this framework at two stages: (1) pyrrhotite with coarse gold and (2) pyrite with fine gold.•A NE-SW ductile strike-slip transport at a convergent tectonic setting with inclined folds plunging to ESE is suggested.•Gold was carried out throughout axial-plane foliation and were placed where coaxial refolding was locally presented.•A post-mineralization tectonic event was responsible for orthogonal displacements at the entire deposit.